Determination of Some Chemical Properties of Uncommon Flours - Andrade, Sónia (2015)
Flours of wheat, chestnut, acorn and lupin were evaluated in relation to phenolic compounds, antioxidant activity, and oxalate content. At the chemical level the results show some variability between samples by type of flour, and the sample of chestnut flour presented the higher value of oxalate (0.00348 mg/100g) when compared to the other samples in the study. Considering the content of phenolic compounds, the sample that stood out was the acorn flour, having a high value of 0.812 g AGE/100 g. All the samples presented intermediate content of antioxidant activity and the sample that showed a slightly higher value was the wheat flour with a value of 0.746 mM TRE/g sample.